Comparative study of the cost and behavior of RC special moment frame buildings with drop and hidden beams subjected to seismic loads - Zúñiga-Olvera, Carlos; Valverde-Burneo, David; Garcia-Troncoso, Natividad; Silva, Christian E.; Gomez, Daniel; Bompa, Dan V. (Frontiers in Built Environment, 2022)
This study presents a comparative analysis between two structural design ideas in the Ecuadorian construction market: hidden vs. drop beams. Due to its location in a high seismic zone, structural design considerations in Ecuador must be carefully made. Therefore, to offer an improved strength to seismic forces, special moment frames are the most common structural system used. However, hidden beams are popular in low story buildings because of a notion of a cheaper system, despite evidence of collapse during earthquake events. In this study we look at special moment frames using hidden type and drop type beams, in terms of cost, structural, and seismic performance. A total of 32 structural models is analyzed, out from which 16 are models of buildings containing hidden beams, and 16 containing drop beams. Linear and nonlinear static analysis, nonlinear local analysis, and moment curvature analysis of the modeled structures are performed to compare their seismic behavior. The structural design is carried out based on linear static analysis for obtaining the total cost of all models. Additionally, a nonlinear static pushover analysis is conducted to assess roof displacement. The evidence shows that when using hidden beams, roof displacement is 20% to 55% higher than when using drop beams, despite the nearly negligible differences in terms of cost. The evidence also shows that structures with drop beams, have 22% to 28% higher nominal flexural moment than structures with hidden beams, while achieving a 27% to 31% higher curvature ductility. This research shows evidence on how structures with drop beams have a better behavior in high seismic risk zones when compared to structures with hidden beams, whose use although allowed, should be limited.